Persuasive effects in social media: the case of envy. Issue 1 (26th October 2020) - Singh, Camille; Ang, Lawrence
Abstract: In the age of social media, consumers are constantly exposed to idealistic images of others arousing social-related emotions such as envy. Yet, very little is known about the effects of envy on purchase intention. Our pilot study and experiment investigated the effects of Facebook envy on purchase intent involving female Facebook users, aged 18–25 years. The pilot study and experiment manipulated the envy subtypes (benign and malicious). A serial mediation model via two mediators to purchase intent was then tested. It tested the persuasion pathway via attitude towards the brand user (human-related social effect) and via the brand (brand-related effect). Results indicated that the human-related social effect was stronger than the brand-related effect. Further analysis into product types (body-related vs non-body-related) found that not all products induce invidious reactions. The effects were only present for the body-related products.